Synthesis of N-Substituted Benzamide Derivatives and their Evaluation as Antitumor Agents - Chen, Taiping; Jiang, Hongwu; Zhou, Jianjun; Li, Zicheng; Huang, Wencai; Luo, Youfu; Zhao, Yinglan (Medicinal Chemistry, 2020)
Background: Histone deacetylases inhibitors (HDACIs) with different chemical structures have been reported to play an important role in the treatment of cancer. Objective: The study aims to modify the structure of Entinostat (MS-275) to discover new compounds with improved anti-proliferative activities and perform SAR studies on this class of bioactive compounds. Methods: Fourteen N-substituted benzamide derivatives were synthesized and their antiproliferative activities were tested with four cancer cell lines (MCF-7, A549, K562 and MDA-MB- 231) by MTT assay. Results: Compared with MS-275, six compounds exhibited comparable or even better antiproliferative activities against specific/certain cancer cell lines. Conclusion: The preliminary SARs showed that (i) the 2-substituent of the phenyl ring in the R group and heteroatoms of amide which can chelate with zinc ion are critical to the antiproliferative activity and (ii) chlorine atom or nitro-group on the same benzene ring largely decreases their anti-proliferative activity. Molecular docking study illustrated the interaction (binding affinity) between the synthesized compounds and HDAC2 was observed to be similar to that of MS-275.
Keywords: SAR studies